MS-150-10-f01-008: Letter to an Unknown Madam, No Date - Arnold, Edwin, Sir, 1832-1904 (Valdosta, GA: Valdosta State University Archives and Special Collections, 1890)
Letter to an unknown Madam regarding a book she inscribed to him. Undated. Old address marked through with new address provided: 45 Kensington Park Gardens.
1 handwritten letter, 3 pages.
Keywords: Personal correspondence; Letters; Arnold, Edwin, Sir, 1832-1904; Poets--Correspondence